2011
DOI: 10.1126/science.1203801
|View full text |Cite
|
Sign up to set email alerts
|

Negative Epistasis Between Beneficial Mutations in an Evolving Bacterial Population

Abstract: Epistatic interactions between mutations play a prominent role in evolutionary theories. Many studies have found that epistasis is widespread, but they have rarely considered beneficial mutations. We analyzed the effects of epistasis on fitness for the first five mutations to fix in an experimental population of Escherichia coli. Epistasis depended on the effects of the combined mutations--the larger the expected benefit, the more negative the epistatic effect. Epistasis thus tended to produce diminishing retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
657
13
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 539 publications
(749 citation statements)
references
References 38 publications
55
657
13
2
Order By: Relevance
“…In this case, the assayed population may be far from its optimum in the new environment, increasing the likelihood a mutation will be beneficial, as has been observed with experimental studies of microorganisms (Burch & Chao, 1999; Khan, Dinh, Schneider, Lenski, & Cooper, 2011; Kryazhimskiy, Rice, Jerison, & Desai, 2014; MacLean, Perron, & Gardner, 2010; Perfeito, Sousa, Bataillon, & Gordo, 2014) and in one field study with A. thaliana (Stearns & Fenster, 2016). It is also possible that there was within‐plant selection during the propagation of the mutation accumulation lines (Otto & Orive, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…In this case, the assayed population may be far from its optimum in the new environment, increasing the likelihood a mutation will be beneficial, as has been observed with experimental studies of microorganisms (Burch & Chao, 1999; Khan, Dinh, Schneider, Lenski, & Cooper, 2011; Kryazhimskiy, Rice, Jerison, & Desai, 2014; MacLean, Perron, & Gardner, 2010; Perfeito, Sousa, Bataillon, & Gordo, 2014) and in one field study with A. thaliana (Stearns & Fenster, 2016). It is also possible that there was within‐plant selection during the propagation of the mutation accumulation lines (Otto & Orive, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…For example, several studies have examined specific examples of epistasis causing evolutionary contingency [12,13]. Other studies have demonstrated a trend for beneficial mutations to interact antagonistically, causing the rate of adaptation to slow as beneficial mutations accumulate [8,9,15], a relationship predicted by theory [16].…”
Section: Introductionmentioning
confidence: 99%
“…This dependence, known as epistasis, is important to many areas of developmental and evolutionary biology, including speciation [1][2][3][4], the maintenance of sex [5,6], adaptation [7][8][9], the evolution of ploidy [10] and evolutionary contingency [11 -14]. As the technology to identify and manipulate specific mutations becomes increasingly available, the influence of epistasis can be examined directly.…”
Section: Introductionmentioning
confidence: 99%
“…La question dès lors se pose des interactions entre ces mutations bénéfiques. Des résultats limités récents ont montré une action épistatique négative entre des mutations bénéfiques, avec décé-lération de l'adaptation [10,11]. Une telle action épistatique négative a été retrouvée dans les données du travail décrit ci-dessus avec des quasi-exclusions de mutations (la présence de mutation au codon 17 du gène rho est en complète répulsion avec la mutation au codon 966 de rpoB).…”
Section: Epidémie De Burkholderia Dolosa : Opportunité D'analyse D'évunclassified